Primer Construction to detect SNP rs11196205 Transcription Factor 7 Like 2 (TCF7L2) Using Amplification Refractory Mutation System (ARMS) PCR to detect Type-2 Diabetes Mellitus - Elsa Badriyya; Afifatul Achyar (Bioscience, 2020)
Type-2 Diabetes Mellitus (T2DM) is a metabolic disease characterized by an increase in blood glucose levels. The macrovascular and microvascular complications of T2DM can increase the risk of death in patient. SNP rs11196205 Transcription Factor 7 Like 2 (TCF7L2) gene has been associated with T2DM in several regions like Iceland, Denmark, the United State, and Thailand. SNP rs11196205 is characterized by polymorphism at position 113.047.288 from nucleotide Guanine to Cytosine. Amplification Refractory Mutation System Polymerase Chain Reaction (ARMS PCR) is a method that can be used to detect mutation or polymorphism in a DNA. The aim of this research was to design a specific primer to detect SNP rs11196205 TCF7L2 gene using ARMS PCR. The design of study was a descriptive study to determine the specific primer. The method of the research includes DNA isolation, primer design using Geneious software, amplification of targeted area using ARMS PCR, and DNA sequencing method for bioinformatics study. Based on the research, four primers to detect SNP rs11196205 TCF7L2 gene have been successfully constructed. The primers were rs11196205-F, rs11196205-R, rs11196205-F(C) as a specific primer for C allele, and rs11196205- R(G) to detect G allele, the reaction produced 3 fragments of 856bp, 559bp, and 339bp.